Features of training programs of highly qualified athletes in cyclic disciplines, where the duration of competitive activity exceeds 6 minutes - Kryuchkov, A. S.; Kryazhev, V. D. (Theory and Practice of Physical Culture, 2025)
Objective of the study - is to establish the characteristics of the training work of the world's leading athletes specializing in sports disciplines where cyclical movements prevail and endurance is required.